(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
The epidermal characters of leaves and anatomical characters of petioles and young stems of some members of the genus Chrysophyllum, viz. C. albidum, C. perpulchrum, C. cainito, and C. delevoyi were analyzed to determine their diagnostic features. Paracytic stomata, crystal sand, prismatic crystals, secretory canals occurred in all the species. All the species are hypostomatic except C. perpulchrum. The midribs of all species have an open semi-circular vascular system except in C. cainito with a closed system. Midrib and petiole of C. albidum and C. cainito have non-glandular T-shaped trichomes. Accessory bundles are only seen in the petioles of C. delevoyi, and in the midribs of C. albidum and C. cainito. The midrib and petiole of C. delevoyi and C. albidum have a central bundle. Laticifers, prismatic and sand crystals occur mainly in the cortical cells, pith cells, xylem, phloem, and mesophyll. Lamina of all species studied showed uniseriate epidermis except C. cainito which has two layers of the adaxial epidermis. The stomatal index, the ratio of the spongy to palisade mesophyll thickness, the ratio of cortex thickness, outline, number, and arrangement of the vascular bundles in the midrib, petiole, and young stem differ and are valuable diagnostic features in Chrysophyllum. Bangladesh J. Plant Taxon. 28(1): 217-231, 2021 (June)